Netrin-1 Ameliorates Postoperative Delirium-Like Behavior in Aged Mice by Suppressing Neuroinflammation and Restoring Impaired Blood-Brain Barrier Permeability - Li, Ke; Wang, Jiayu; Chen, Lei; Guo, Meimei; Zhou, Ying; Li, Xiaofeng; Peng, Mian (Frontiers in Molecular Neuroscience, 2022)
Postoperative delirium (POD) is a common and serious postoperative complication in elderly patients, and its underlying mechanism is elusive and without effective therapy at present. In recent years, the neuroinflammatory hypothesis has been developed in the pathogenesis of POD, in which the damaged blood-brain barrier (BBB) plays an important role. Netrin-1, an axonal guidance molecule, has been reported to have strong inflammatory regulatory and neuroprotective effects. We applied Netrin-1 (45 μg/kg) to aged mice using a POD model with a simple laparotomy to assess their systemic inflammation and neuroinflammation by detecting interleukin-6 (IL-6), interleukin-10 (IL-10), and high mobility group box chromosomal protein-1 (HMGB-1) levels. We also assessed the reactive states of microglia and the permeability of the BBB by detecting cell junction proteins and the leakage of dextran. We found that a single dose of Netrin-1 prophylaxis decreased the expression of IL-6 and HMGB-1 and upregulated the expression of IL-10 in the peripheral blood, hippocampus and prefrontal cortex. Nerin-1 reduced the activation of microglial cells in the hippocampus and prefrontal cortex and improved POD-like behavior. Netrin-1 also attenuated the anesthesia/surgery-induced increase in BBB permeability by upregulating the expression of tight junction-associated proteins such as ZO-1, claudin-5 and occludin. These findings confirm the anti-inflammatory and BBB protective effects of Netrin-1 in an inflammatory environment in vivo and provide better insights into the pathophysiology and potential treatment of POD.